It’s a Journey: A Graphic Medicine Exploration of Endometriosis and Gender Diversity - Maddalena Giacomozzi; Stéphane Guy Aubin; Elisa Castellano; Jasmine Brazelton; Max Jahufer; Jip Bouwens; Donna Ruumpol; Khushi Jeswani; M Mainetti; Maaike Muntinga; Petra Verdonk; Annemiek W. Nap (Journal of Participatory Research Methods)
Transgender and gender diverse (TGD) individuals assigned female at birth (AFAB) are greatly impacted by endometriosis, which can severely affect their quality of life. This group faces significant barriers to healthcare due to structural discrimination and marginalization. Their experiences are often silenced, and healthcare professionals (HCPs) lack training to adequately diagnose and treat them. A TGD-led group implemented graphic medicine methodology to research endometriosis and gender diversity within a participatory action research (PAR) approach. Participants had diverse backgrounds and contributed to the project thanks to a combination of their real lived experiences and their professional expertise. In this report, we use a participatory action research (PAR) approach to implement a graphic medicine initiative on endometriosis and gender diversity. Graphic medicine is a methodology that combines healthcare and visual storytelling to enhance understanding of medical experiences and is a particularly suitable method for recentering experiences of marginalized communities and empowering them through the development of a knowledge product. The participants who contributed to the development of the graphic medicine product had diverse backgrounds and contributed both their real lived experiences and professional expertise. A comprehensive graphic medicine product was eventually developed, incorporating three key components: (1) a biographical narrative of a representative nonbinary transmasculine individual with endometriosis, (2) anonymized quotes from focus groups with TGD individuals, capturing diverse lived experiences, and (3) educational content aimed at HCPs on combining endometriosis treatment with gender-affirming care. Available in English, both online and in hardcopy, the product is currently used for educational, clinical training, and scientific purposes. Feedback from early users suggests its effectiveness in enhancing awareness and understanding among HCPs of endometriosis, gender diversities, and the intersections thereof.